2009
DOI: 10.1016/j.apacoust.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Double-leaf microperforated panel space absorbers: A revised theory and detailed analysis

Abstract: A double-leaf microperforated panel space absorber (DLMPP) is composed of two microperforated panels (MPPs) placed in parallel with an air-cavity in-between, without a back wall or any backing structure. This was proposed as a space sound absorber, which can be used for a sound absorbing screen or partition. A conventional MPP absorber with a rigid back wall is effective only around its resonance frequency, which is usually at middle frequencies, and not effective at low frequencies. However, a DLMPP can be ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 9 publications
0
49
0
1
Order By: Relevance
“…In the present paper, a novel approach to the double MPP absorber by using strict wave theory based on Helmholtz-Kirchhoff integral formulation [15][16][17][18] is proposed. Although ITM and its similar approach can be well used to obtain correct solution for multiple layer absorption structures including double-leaf MPPs, Helmholtz-Kirchhoff integral formulation is more general and expandable, which can be extended to the cases where various other construction (e.g., elastic support, honeycomb in the cavity, etc., that will be dealt with in further studies) are included.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, a novel approach to the double MPP absorber by using strict wave theory based on Helmholtz-Kirchhoff integral formulation [15][16][17][18] is proposed. Although ITM and its similar approach can be well used to obtain correct solution for multiple layer absorption structures including double-leaf MPPs, Helmholtz-Kirchhoff integral formulation is more general and expandable, which can be extended to the cases where various other construction (e.g., elastic support, honeycomb in the cavity, etc., that will be dealt with in further studies) are included.…”
Section: Introductionmentioning
confidence: 99%
“…The air gap/volume behind the MPP provides an acoustic stiffness, 4 which leads to resonance-type absorption with the perforation. This cavity-backed MPP finds its use in various system configurations and therefore deserves a particular treatment.…”
Section: Equivalent Ptfs For a Cavity-backed Mppmentioning
confidence: 99%
“…This is done in Fig. 7, in which the impedance of the MPP, @S=W, is compared to that of the cavity Z ii for one particular patch (3,4). It can be seen that, @S=W are generally larger than Z ii , except for frequencies close to the natural frequencies of the cavity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the total thickness of the absorber can be decreased. There are various types of MPP absorbers designed to improve the absorption performance [12][13][14]. Besides, it is found that sound-induced vibration of MPPs can affect the sound absorption of the systems and many research studies have been carried out on this topic.…”
mentioning
confidence: 99%